2020
DOI: 10.1097/icu.0000000000000722
|View full text |Cite
|
Sign up to set email alerts
|

Use of presbyopia-correcting intraocular lenses in patients with prior corneal refractive surgery

Abstract: Purpose of review Corneal refractive surgery has achieved spectacle-free vision for millions of patients, but this aging population is now developing cataracts. Many of these patients may wish to avoid reliance on glasses after cataract surgery. Presbyopia-correcting intraocular lenses (IOLs) offer a solution, but corneal changes after refractive surgery may compound higher order aberrations and dysphotopic symptoms associated with these IOLs. This review aims to discuss potential factors that coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Among the HOAs, coma, trefoil, and spherical aberration are known as visually significant aberrations; the vertical coma and spherical aberration are known as the two major HOAs that clinically significantly increase in keratoconus patients [10,11], and are related to visual acuity and discomfort after cataract surgery patients [12][13][14]. In addition, as the number of premium cataract surgeries using multifocal or toric intraocular lens (IOL) gains popularity in patients who had corneal refractive surgery, cut-off values of HOAs are suggested for those patients to prevent postoperative suboptimal visual outcome and patient's dissatisfaction [15]. Therefore, measuring corneal HOAs is essential for predicting and interpreting visual performance under various conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Among the HOAs, coma, trefoil, and spherical aberration are known as visually significant aberrations; the vertical coma and spherical aberration are known as the two major HOAs that clinically significantly increase in keratoconus patients [10,11], and are related to visual acuity and discomfort after cataract surgery patients [12][13][14]. In addition, as the number of premium cataract surgeries using multifocal or toric intraocular lens (IOL) gains popularity in patients who had corneal refractive surgery, cut-off values of HOAs are suggested for those patients to prevent postoperative suboptimal visual outcome and patient's dissatisfaction [15]. Therefore, measuring corneal HOAs is essential for predicting and interpreting visual performance under various conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no explicit guidance exists to preclude the use of presbyopia-correcting IOLs regarding the amount of spherical aberrations or other HOAs. It is suggested that potential MIOLs contraindication thresholds for total HOAs was >2.0 SD ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed that both SMILE and wavefront-guided-LASIK result in a similar increase in total HOAs, with wavefront-guided-LASIK causing more spherical aberrations and SMILE causing more vertical coma and trefoil [46]. As presbyopia-correcting IOLs may potentially further exacerbate HOAs in eyes with prior CRS, implantation of these IOLs in CRS-treated eyes is generally not recommended and should only be used after thorough preoperative patient counselling and careful patient selection; for instance, in eyes with small amount of HOAs and more regular astigmatism [47,48].…”
Section: Refractive Target and Spectacles Independencementioning
confidence: 99%